RSV prevention in adults: consensus of experts of Polish scientific societies - Antczak, Adam; Barczyk, Adam; Biesiada, Aleksander; Czajkowska-Malinowska, Małgorzata; Flisiak, Robert; Gil, Robert; Grabowski, Marcin; Kania, Aleksander; Konstanty, Mikołaj; Krenke, Rafał; Kuchar, Ernest; Mamcarz, Artur; et al. (Family Medicine & Primary Care Review, 2025)
Respiratory syncytial virus (RSV) is a respiratory pathogen that can cause severe infections and exacerbate underlying conditions in older adults and individuals with comorbidities. While infection in healthy adults is usually mild, in at-risk populations, RSV may lead to worsening of chronic diseases, hospitalization, or even death. Epidemiological surveillance data from Poland indicates a dynamic increase in the number of confirmed RSV infections, driven by broader access to diagnostics. In parallel, the number of hospitalizations due to RSV infection has also increased. Vaccination against RSV represents a new preventive strategy. Although vaccines registered in 2023–2024 provide only limited protection against infection itself, they are effective in preventing severe disease and its complications. Vaccines may be administered year-round, as protection extends minimally across two infection seasons. Since 2024, RSV vaccination in Poland has been publicly funded based solely on demographic criteria. Thus, to maximize the benefits of this preventive measure, universal vaccination is recommended for all individuals ≥ 65 years of age, as well as vaccination of adults aged 60–64 years with risk factors for severe RSV disease. Younger adults should also consider vaccination, especially when multiple comorbid conditions accumulate. Risk factors include chronic cardiovascular and respiratory diseases, diabetes, obesity, and immunocompromising conditions.